The Effect of The Hurdle Hops, Multiple Box Jumps, and Dogging Run Training Methods on Football Shooting Skills - Ridwan, Andi; Asmawi, Moch.; Dlis, Firmansyah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study is an experimental study that aims to determine the effect of hurdle hops, multiple box jumps, and dogging run training methods on football shooting skills. The subjects in this study were students of the Faculty of Sports Science (FIK) Universitas Negeri Makassar (UNM), totaling 60 students divided into 3 groups, each group consisting of 20 students. The data analysis technique used the Tukey test with a significance level of 0.05. The results of the analysis of research data obtained that the average football shooting score for the hurdle hops training method group was 38.90, the multiple box jumps exercise method group was 27.85, and the dogging run exercise method group was 22,75. The results of this study indicate that of the three training methods given to each group, the results obtained that the hurdle hops exercise method has the greatest influence on football shooting skills in football games compared to multiple box jumps and dogging runs.